4 times 2= 8. so, 4times k2 = k8. To understand this better, imagine that k equaled 2. That would make the expression above = (2x2)4, which would equal 16. However, since we don't know the value of k, we have to use the numbers that we already have, It would be like solving the expression: (2x2)4 without multiplying the first 2. It would then be 2x8. So, we just simplified it, we didn't solve it.
Answer:
2(x-5)(x+4)
Step-by-step explanation:
2x^2 − 2x − 40
Factor out a 2
2(x^2 -x -20)
What 2 numbers multiply to -20 and add to -1
-5*4 = -20
-5+4 = -1
2(x-5)(x+4)
The car can travel 75 miles on 2 1/2 gal. of gas
Answer:
It has no real solution.
Step-by-step explanation:
6p^2 − 7p + 5 = 0
For this equation: a = 6, b = -7, c = 5
6p^2+ −7p + 5 = 0
Step 1: Use quadratic formula with a=6, b=-7, c=5.
p = -b ± √b^2 - 4ac/2a
p = -(-7) ± √(-7)^2 - 4(6)(5)/2(6)
p = 7 ± √-71/12